The Concepts of the Logos in Philo of Alexandria - Todorovska, Marija (Živa Antika & The Faculty of Philosophy, Skopje, 2015)
Philo of Alexandria offers versatile and many-layered approaches to the understanding of the Logos in Scripture, applying a philosophical apparatus to holy texts in order to explore the rich ontological, theological and anthropological sphere of the manifold concept. Some of the main concepts that he uses in his extensive analysis of the status, nature, functions and meaning of the Logos intertwine and coincide, and some seem to exclude one another, depending on the way of interpretation of certain passages of his works. The main concepts of the Logos briefly overviewed in the present article are: “second God” and the ontological and methodological connection between them, along with Philo’s apophatic convictions; an utterance of God, whose words and deeds strictly correspond; a Word of God; “Son” of God; a divine archetype – both a blueprint and a place for Ideas and a thought eternally produced by God, an object of thinking and an essence permeating everything else which is thought/created; a principle of creation and differentiation in the world; a bond which orders and controls physical laws and spiritual and corporeal relations; an intermediary principle of power which serves not only as a messenger or agent of God, but as his attribute, his exteriorisation, his otherwise transcendent existence rendered present and involved in earthly matters; a multi-named archetype; wisdom of God and immanent wisdom which guides human intellects in their contemplation and virtue.